Quantifying and specifying the solar influence on terrestrial surface temperature - de Jager, C. (2010)
This investigation is a follow-up of a paper in which we showed that both major magnetic components of the solar dynamo, viz. the toroidal and the poloidal ones, are correlated with average terrestrial surface temperatures. Here, we quantify, improve and specify that result and search for their causes. We studied seven recent temperature files. They were smoothed in order to eliminate the Schwabe-type (11 years) variations. While the total temperature gradient over the period of investigation (1610-1970) is 0.087 °C/century; a gradient of 0.077 °C/century is correlated with the equatorial (toroidal) magnetic field component. Half of it is explained by the increase of the Total Solar Irradiance over the period of investigation, while the other half is due to feedback by evaporated water vapour. A yet unexplained gradient of -0.040 °C/century is correlated with the polar (poloidal) magnetic field. The residual temperature increase over that period, not correlated with solar variability, is 0.051 °C/century. It is ascribed to climatologic forcings and internal modes of variation. We used these results to study present terrestrial surface warming. By subtracting the above-mentioned components from the observed temperatures we found a residual excess of 0.31° in 1999, this being the triangularly weighted residual over the period 1990-2008. We show that solar forcing of the ground temperature associated with significant feedback is a regularly occurring feature, by describing some well observed events during the Holocene.